Word Formation Guide for the general public and specialists - Murmulaitytė, Daiva (Lietuvių kalba, 2022)
Word Formation Guide (WFG) – one of the services of the Information System of Resources of the Lithuanian Language E. kalba (E -Language). It is intended to quickly and concisely introduce the means of word formation of Lithuanian nouns and the essential regularities of their formation. This guide is intended for the general public, but may also be useful for the specialists in word formation. The article briefly introduces a fast and detailed data search in the WFG. The quick search provides two ways of searching for means of word formation, focusing on their formal expression or derivative and lexical semantics. The detailed search is designed to search according to several features of the word formation means, base, and the semantics of the derivatives. In this search various combinations of the features are possible. Next, the article discusses several problematic issues that arose during the creation of the WFG data structure and data management. This is the homonymy of means of word formation, the classification of initial and final borrowed (neoclassical and other) formatives of words (prefixes, combining forms etc.) and their place in the word formation system of the Lithuanian language, and in the guide under discussion, experimental separation of (lexical) semantic features. In conclusion, the development possibilities of the Word Formation guide are introduced, not only by increasing the number of examples of noun derivatives and compounds but also by redesigning the current data structure and including the word formation data of other parts of speech.